The leader's guide to coaching in schools : creating conditions for effective learning - Campbell, John, active 2018; Nieuwerburgh, Christian van (Thousand Oaks : Corwin, 2018)
Grow your leadership skills to bring out the best in your school! Hallways, parking lots, staff rooms-these are all places where you and your staff have conversations every day. What if you could use these opportunities to build your staff's resiliency and empower them to reach their goals. The Leader's Guide to Coaching in Schools offers a proven, accessible, and usable framework to increase your interpersonal effectiveness and grow your ability to coach your staff to overcome obstacles and create their own solutions. Coaching experts John Campbell and Christian van Nieuwerburgh demonstrate how coaching is not just for formal coaching relationships, but how a coaching approach can be applied throughout a school day to create a culture of growth. Through sample questions, video examples, and tools this step-by-step guide shows you how to: Introduce a coaching approach into a wide range of conversational contexts Use the GROWTH coaching conversation framework to improve both staff and student success and well-being Use coaching approaches in areas that school leaders typically find challenging: in formal performance reviews, when giving informal feedback, and when working with teams Help your staff get'unstuck' no matter what challenges they are facing by using solutions-focused coaching techniques that help them envision desired outcomes and the actions needed to achieve them.'The GROWTH coaching model should be in every administrator's hand as their bible for school improvement. Having this guide will guarantee success and getting the best out of all stakeholders.' -Elizabeth Alvarez, Principal John C. Dore Elementary, Chicago, IL'The book is just what the doctor ordered for busy leaders-short and concise.' -B.R. Jones, Superintendent of Education Tate County School District, Senatobio, MS.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Educational leadership; Mentoring in education; School management and organization; School administrators